Adverse events related to prenatal: an epidemiological study (Research, Society and Development, 2022)
Prenatal care (PC) is an important tool in maintaining the health of pregnant woman and fetus, being important in reducing deaths and the appearance of complications. For this, the Ministry of Health (MH) instituted the Programa de Humanização no Pré-Natal e Nascimento (PHPN), aiming to standardize care and propose a link between PC and childbirth services. The objective of the study was to relate the level of adequacy of PC with the occurrence of adverse events during pregnancy in the state of Minas Gerais. It is a documentary, descriptive, exploratory, cross-sectional and retrospective study, of quantitative nature. Data were extracted from the Sistema de Informação sobre Nascidos Vivos (SINASC), and included pregnant women who underwent prenatal care, in the period between 2015-2020. Data were processed using SPSS version 25.0. We opted for the chi-square test for bivariate analysis (p